Evaluation of medicinal plants as potential food antimicrobial additives (Research, Society and Development, 2020)
Foodborne diseases still represent a public health problem worldwide. The resistance of microrganisms to various antibiotics has been stimulating research aimed at the discovery of new substances with natural antimicrobial action. The objective of this study was to evaluate the potential use of plants commonly used in folk medicine as antimicrobials. The decocts were submitted to the analysis of antimicrobial activity for Listeria monocytogenes, Salmonella Enteritidis, Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa by the microdilution technique. Croton blanchetianus stem bark extract presented the best results, being effective on all microrganisms tested in concentrations of 0.5 to 19 mg / mL. For the extract of the bark of the Myracrodruon urundeuva stem only activity on E. coli was not verified. The stem bark extract of Croton nepetaefolius showed activity on S. aureus and S. Enteritidis and only inhibitory for L. monocytogenes. The leaf extract of Sideroxylon obtusifolium was not effective only on E. coli and P. aeruginosa. In view of this, the aqueous extracts of these plants appear as a new source of substances with antibacterial potential for application in the food industry.